Experimental investigation on the yield behavior of Nomex honeycombs under combined shear-compression - Zhou,Zhiwei (2012)
This paper presents an experimental investigation on the yield behavior of Nomex honeycombs under combined shearcompression with regard to out-of-plane direction. Four different types of specimens were designed in order to investigate the influence of in-plane orientation angle on the yield behavior of honeycombs under combined loads. Two different failure modes of honeycomb specimens, i.e. the plastic buckling and the extension fracture of cell walls, are observed under combined shear-compression. The experimental results validate that the in-plane orientation angle has a significant influence on the developments of the experimental yield surface. The experimental yield surfaces are compared with a phenomenological yield criterion capable of accounting for anisotropic behavior. The comparative analytical results indicate the experimental yield surfaces are approximately consistent with the theoretical yield surfaces in the normal-shear stress space. These experimental results are useful to develop constitutive models of Nomex honeycombs under combined shear-compression.